Integrated proteomics and genomics analysis of paradoxical eczema in psoriasis patients treated with biologics - Al-Janabi, A.; Martin, P.; Khan, A. R.; Foulkes, A. C.; Smith, C. H.; Griffiths, C. E. M.; Morris, A. P.; Eyre, S.; Warren, R. B.; Group, Bstop Study; the, Badbir Study Group (J Allergy Clin Immunol, 2023)
BACKGROUND: Few studies have explored the immunology and genetic risk of paradoxical eczema occurring as an adverse event of biologic therapy in patients with psoriasis. OBJECTIVES: We sought to describe the systemic inflammatory signature of paradoxical eczema using proteomics and explore whether this is genetically mediated. METHODS: This study used the Olink Target 96 Inflammation panel on 256 serum samples from 71 patients with psoriasis and paradoxical eczema, and 75 controls with psoriasis to identify differentially expressed proteins and enriched gene sets. Case samples from 1 or more time points (T1 prebiologic, T2 postbiologic, and T3 postparadoxical eczema) were matched 1:1 with control samples. Genes contributing to enriched gene sets were selected, and functional single nucleotide polymorphisms used to create polygenic risk scores in a genotyped cohort of 88 paradoxical eczema cases and 3124 psoriasis controls. RESULTS: STAMBP expression was lower in cases at T1 than in controls (log-fold change: -0.44; adjusted P = .022); no other proteins reached statistical significance at equivalent time points. Eleven gene sets including cytokine and chemokine pathways were enriched in cases at T2 and 10 at T3. Of the 39 proteins contributing to enriched gene sets, the majority are associated with the atopic dermatitis serum proteome. A polygenic risk score including 38 functional single nucleotide polymorphisms linked to enriched gene sets was associated with paradoxical eczema (adjusted P = .046). CONCLUSIONS: The paradoxical eczema systemic inflammatory proteome trends toward atopic dermatitis at a gene-set level and is detectable before onset of the phenotype. This signature could be genetically determined.